Respuesta :

Answer:

[tex]\frac{1}{7}-3(\frac{3}{7}n-\frac{2}{7})=1-\frac{9}{7}n[/tex]

Step-by-step explanation:

Given : Expression [tex]\frac{1}{7}-3(\frac{3}{7}n-\frac{2}{7})[/tex]

To find : Combine like terms to create an equivalent expression ?

Solution :

Step 1 - Write the expression,

[tex]\frac{1}{7}-3(\frac{3}{7}n-\frac{2}{7})[/tex]

Step 2 - Apply distributive property, [tex]a(b+c)=ab+ac[/tex]

[tex]=\frac{1}{7}-3\times \frac{3}{7}n+3\times \frac{2}{7}[/tex]

[tex]=\frac{1}{7}-\frac{9}{7}n+\frac{6}{7}[/tex]

Step 3 - Combine like terms,

[tex]=\frac{1}{7}+\frac{6}{7}-\frac{9}{7}n[/tex]

[tex]=\frac{1+6}{7}-\frac{9}{7}n[/tex]

[tex]=\frac{7}{7}-\frac{9}{7}n[/tex]

[tex]=1-\frac{9}{7}n[/tex]

Therefore,  [tex]\frac{1}{7}-3(\frac{3}{7}n-\frac{2}{7})=1-\frac{9}{7}n[/tex]

Answer:

Step-by-step explanation:

Given : Expression To find : Combine like terms to create an equivalent expression ?Solution : Step 1 - Write the expression,Step 2 - Apply distributive property, Step 3 - Combine like terms,Therefore,  

Read more on Brainly.com - https://brainly.com/question/14172736#readmore